Mobility and Policy Responses During the COVID-19 Pandemic in 2020 - Cepaluni, Gabriel [UNESP]; Dorsch, Michael T.; Kovarek, Daniel (Frontiers, 2022)
Objective: This paper quantitatively explores determinants of governments’ non-pharmaceutical policy responses to the COVID-19 pandemic. Our focus is on the extent to which geographic mobility affected the stringency of governmental policy responses. Methods: Using cross-country, daily frequency data on geographic mobility and COVID-19 policy stringency during 2020, we investigate some of the determinants of policy responses to COVID-19. In order to causally identify the effect of geographic mobility on policy stringency, we pursue an instrumental variable strategy that exploits climate data to identify arguably exogenous variation in geographic mobility. Results: We find that societies that are more geographically mobile have governmental policy responses that are less stringent. Examining disaggregated mobility data, we show that the negative relation between geographic mobility and policy stringency is the stronger for commercially-oriented movements than for geographic movements that relate to civil society. Conclusion: The results suggest that policy-makers are more willing to trade-off public health for economic concerns relative to other civil concerns.
Keywords: COVID-19; geographic mobility; high-frequency panel data; instrumental variables; policy responses